Cover Picture: Alumina‐Supported Alpha‐Iron(III) Oxyhydroxide as a Recyclable Solid Catalyst for CO2 Photoreduction under Visible Light (Angew. Chem. Int. Ed. 26/2022). Issue 26 (1st June 2022) - An, Daehyeon; Nishioka, Shunta; Yasuda, Shuhei; Kanazawa, Tomoki; Kamakura, Yoshinobu; Yokoi, Toshiyuki; Nozawa, Shunsuke; Maeda, Kazuhiko
Abstract : An iron‐based oxyhydroxide catalyst was developed for CO2 photoreduction into formic acid. As reported by Kazuhiko Maeda et al. in their Communication (e202204948 ), α‐iron(III) oxyhydroxide, which is an easily available soil mineral, was loaded onto an alumina support and then serves as a recyclable catalyst for the CO2 reduction reaction, showing 80–90 % selectivity and an apparent quantum yield of 4.3 % at 460 nm in the presence of a ruthenium(II) photosensitizer and an electron donor.